Visual culture and the style of college textbooks: a critical study - Molek-Kozakowska, Katarzyna (Stylistyka, 2019)
This article aims at exploring and problematizing the role of visual designs, as applied in a selection of five popular recent college textbooks that introduce students to Cultural and Media Studies. It can be observed that academic textbooks are increasingly produced in alignment with the properties of contemporary visual culture. The article reviews some of these properties, focusing on the growing need for enhancing visual literacy. It presents the framework of multimodal analysis, as the textbook is co-constituted by verbal and visual modes, which are integrated through a common design. The analytic categories of multimodal analysis allow for a qualitative, yet systematic, examination of some compositional and semiotic resources that have been applied in textbooks. The analysis focuses on textbook typography, supra-textual organization, the number and choice of figures/tables/lists, the layout of pages, structure of chapter/section, and type and framing of visuals. This is followed by a function-oriented critical discussion of these stylistic properties and of the implications of certain compositional preferences for teaching/learning. The study identifies designs that result in diversifying and aestheticizing textbooks visually, as well as hierarchizing and objectivizing knowledge. While both advantages and disadvantages of currently popular designs can be found, attention is drawn to the fact that visually-enhanced designs might fail to engage students in critical reflection, simplify the issues, and divert attention from the merits of exposition/argument, particularly if students lack skills in visual literacy.